PRODUCTION AND CHARACTERIZATION OF BIOSURFACTANT (GLYCOLIPID) FROM LACTOBACILLUS HELVITICUS M5 AND EVALUATE ITS ANTIMICROBIAL AND ANTIADHESIVE ACTIVITY - & Haydar, Kadhum (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The current study was aimed to optimize, characterize and evaluate the antimicrobial and antiadhesive activity of biosurfactant(glycolipid) produce from local isolateLactobacillus helvetiusM5. The obtained results indicate that the highest emulsifying activity occurred at pH 7, Lactose (5%) the best production medium, 1% peptone as nitrogen source, maximum growth and production of biosurfactant was observed at C: N ratio (5:1) and after 120 h of incubation. Partial purified biosurfactant was characterized byfourier transform infrared spectroscopy and gas chromatography mass. FTIR results indicated aliphatic hydrocarbon chains along with a polysaccharide moiety that confirmed the glycolipid nature of the biosurfactant produced . GC analysis of glycolipid indicated the cycle aliphatic lipid nature of the structures in the biosurfactant.Antibacterial and antiadhesion activities of biosurfactant were evaluated against some pathogenic bacteria. The biosurfactant showed inhibition zones diameter ranged from (12 to 29 mm) and (15 to 31 mm) against P. aeruginosa and S. aureus respectively at concentration of glycolipid ranged from 20 to 100 mg/ml.The highest antiadhesive property was observed against S. aureus (78%) and P. aeruginosa (74.5%) at concentration 50 mg/ml of glycolipid respectively.